The Neoconservative persuasion: selected essays, 1942-2009 - Kristol, Irving (New York: 1a. ed, 2011)
Contiene: In the beginning. Ancients and moderns. Democracy in America. The culture and counterculture. Capitalism, conservatism, and neoconservatism. Foreign policy and ideology. Judaism and christianity
Keywords: Conservatism - United States